The diversification of terpene emissions in Mediterranean oaks: lessons from a study of Quercus suber, Quercus canariensis and its hybrid Quercus afares - Welter, Saskia; Bracho-Nuñez, Araceli; Mir, Celine; Zimmer, Ina; Kesselmeier, Jürgen; Lumaret, Roselyne; Schnitzler, Jörg-Peter; Staudt, Michael (Tree Physiology, 2012)
Interspecific gene flow is common in oaks. In the Mediterranean, this process produced geographical differentiations and new species, which may have contributed to the diversification of the production of volatile terpenes in the oak species of this region. The endemic North African deciduous oak Quercus afares (Pomel) is considered to be a stabilized hybrid between the evergreen Quercus suber (L.) and the deciduous Quercus canariensis (Willd.), presumably being monoterpene and isoprene emitters, respectively. In a common garden experiment, we examined the terpene emission capacities, terpene synthase (TPS) activities and nuclear genetic markers in 52 trees of these three oak species. All but one of the Q. suber and Q. canariensis trees were found to be genetically pure, whereas most Q. afares trees possessed a mixed genotype with a predominance of Q. suber alleles. Analysis of the foliar terpene emissions and TPS activities revealed that all the Q. canariensis trees strongly produced isoprene while all the Q. suber trees were strong monoterpene producers. Quercus afares trees produced monoterpenes as well but at more variable and significantly lower rates, and with a monoterpene pattern different than that observed in Q. suber. Among 17 individuals tested, one Q. afares tree emitted only an insignificant amount of terpenes. No mixed isoprene/monoterpene emitter was detected. Our results suggest that the capacity and pattern of volatile terpene production in Algerian Q. afares populations have strongly diverged from those of its parental species and became quantitatively and qualitatively reduced, including the complete suppression of isoprene production.
10.1093/treephys/tps06910.1093/treephys/tps069
Keywords: Algerian oak; allozyme polymorphism; chemo-taxonomy; chemotype; Cork oak; isoprene synthase; isoprenoid; speciation

Terpenoid emissions of Mediterranean oaks and their relation to taxonomy - Csiky, O.; Seufert, G. (ECOLOGICAL APPLICATIONS, 1999)
This paper presents results of a laboratory screening study of biogenic emissions from Mediterranean oak species. The experiment aimed at improving our understanding of oak contributions to overall emissions of volatile organic compounds and to the atmospheric chemistry in the Mediterranean area. We measured type and amount of terpenoid emissions (isoprene, mono- and sesquiterpenes) under standard conditions of light and temperature from 14 different Quercus species of Mediterranean and American origin. Tree saplings were exposed in a controlled environment chamber, and leaf-level trace-gas exchange was analyzed with a minicuvette system and gas chromatography, to study the relation between the emission types and emission spectra found and the taxonomy of Quercus. The holarctic group Lepidobalanus and the North American groups Erythrobalanus and Protobalanus were found to be strong isoprene emitters. The Eurasian oak group Sclerophyllodrys emits monoterpenes; Cerris include mostly non-emitters, but also an isoprene and a monoterpene emitter has been found in this group. Results are discussed with respect to their implications for presently used emission scenarios.
The following values have no corresponding Zotero field: pub-location: 1707 H ST NW, STE 400, WASHINGTON, DC 20006-3915 USA publisher: ECOLOGICAL SOC AMER
Keywords: atmospheric chemistry; BEMA (Biogenic Emissions in the Mediterranean Area; Biogenic emission; chemo-taxonomy; isoprene; Mediterranean Region; Monoterpenes; oak taxonomy; oaks; Quercus; terpenoid emissions; trace-gas exchange; volatile organic compounds (VOCs)